Raise of short-stemmed vaviloid branched spike lines and their cytogenetics - A. J. Aliyeva; S. P. Mehdiyeva; R. K. Kerimova (Вавиловский журнал генетики и селекции)
Hybridization between hexaploid species of wheat (Triticum L.) and triticale (Ч Triticosecale Wittm.) is used widely in genetic research and breeding when studying mutual introgressions of genetic material to original species. As far as the hexaploid triticale obtained in our Institute possessed a strong potential of morphogenesis, we decided to use it in crosses with bread wheat. During the process of morphogenesis in hybrid population of the second and third generations derived from the crosses between hexaploid triticale with different bread wheat cultivars (Opal and Chinese Spring) and variety (Triticum aestivum var. velutinum), plants with wheat, rye, intermediate, and triticale-like spike types were noted. Starting from the third generation, constant short-stemmed vaviloid branched spike plants were isolated among populations under study. Despite instability and numerous meiotic aberrations observed in the first generation of plants, including branched-spike ones, the subsequent progeny demonstrated meiotic and morphological stability. The chromosome composition of one of the lines (378/3SD) was characterized by fluorescence in situ hybridization (FISH) and genome in situ hybridization (GISH), and it was identified as a substitution line. Chromosomal identification of such lines will allow their use in genetic studies concerning specified traits, in particular, the vaviloid branched spike.